PELATIHAN LITERASI KEUANGAN: PERENCANAAN KEUANGAN UNTUK SISWA SMA DHARMA BAKTI LUBUK PAKAM - Afrizal, Afrizal; Herlambang, Albert; Rezeki, Sri; Sinaga, Hommy Dorthy Ellyany; Loo, Petrus; Tiofanny, Claudie (Smart Education, 2025)
Abstract: In today's digital era, financial literacy has become a crucial skill for the younger generation, especially high school students, to manage their finances effectively and responsibly. This enables them to handle their finances wisely and avoid harmful financial risks. This article discusses the implementation of a financial literacy training held at SMA Dharma Bakti Lubuk Pakam on March 8, 2025, attended by 59 selected students, the results obtained, and recommendations for sustainable financial literacy development within the school environment. The training focused on two main topics: financial planning and understanding online loans. The training aimed to enhance students' knowledge and skills in managing personal finances as well as recognizing the risks and mechanisms of online loans, which are prevalent among teenagers. The training methods included interactive lectures and individual case studies. Keywords: Financial Literacy; Online Loans; Financial Planning; Financial Education; Digital Finance. Abstrak: Di era digital saat ini, literasi keuangan telah menjadi keterampilan yang sangat penting bagi generasi muda khususnya siswa Sekolah Menengah Atas (SMA) untuk mengelola keuangan mereka secara efektif dan bertanggung jawab agar mampu mengelola keuangan secara bijak dan terhindar dari risiko finansial yang merugikan. Artikel ini membahas pelaksanaan pelatihan literasi keuangan yang diadakan di SMA Dharma Bakti Lubuk Pakam pada tanggal 08 Maret 2025, yang diikuti oleh 59 siswa terpilih hasil yang diperoleh, serta rekomendasi untuk pengembangan literasi keuangan yang berkelanjutan di lingkungan sekolah. Pelatihan ini menitikberatkan pada dua topik utama, yaitu perencanaan keuangan dan pemahaman pinjaman online. Pelatihan ini bertujuan untuk meningkatkan pengetahuan dan keterampilan siswa dalam mengelola keuangan pribadi serta mengenali risiko dan mekanisme pinjaman online yang marak di kalangan remaja. Metode pelatihan meliputi ceramah interaktif, dan studi kasus individu. Kata Kunci: Literasi Keuangan; Pinjaman Online; Perencanaan Keuangan; Edukasi Keuangan; Keuangan Digital.